KEMAMPUAN LABA, ARUS KAS OPERASI DALAM MEMPREDIKSI ARUS KAS MASA DEPAN - Andayani, Rai Dwi; Wirajaya, Gede Ary (E-Jurnal Akuntansi; Vol 10 No 3 (2015), 2015)
This study was conducted to determine the level of ability of current operating cash flow, current earnings, current earnings plus depreciation, and operating working capital in predicting future cash flows depan. Sampel were 120 companis in 2011-2013 , using purposive sampling method and non-participant observation. Multiple linear regression was used in this research. Results of statistical t test showed that the operating cash flow has a significant capability, while variable earnings, earnings plus depreciation and operating working capital does not have the ability to predict future cash flows .
Keywords: operating cash flow, earnings, earnings plus depreciation, operating working capital